FEISTY Fortran library and R package to integrate fish and fisheries with biogeochemical models - Yixin Zhao; P. Daniël vanDenderen; Rémy Denéchère; Jonathan E. Falciani; Nis S. Jacobsen; Themistoklis Konstantinopoulos; Daniel Ottmann; Colleen M. Petrik; Karline Soetaert; Charles A. Stock; Ken H. Andersen (Methods in Ecology and Evolution)
Abstract The FishErIes Size and functional TYpe model (FEISTY) is a mechanistic ecosystem model that fully integrates ecosystem structure across trophic levels through functional types. We present an R package that enables users to run simulations ranging from a 0D chemostat to full global scales. The library is written in Fortran90 with an R interface and provides a web application for visual exploration. We present and compare results from four core configurations across a range of depths, productivity and fishing levels, and we assess the convergence of solutions as the number of size classes is increased. The model has historically been coupled to biogeochemical models of mesozooplankton and detritus production, but it can also be applied in a stand‐alone version. We demonstrate the library to set up and simulate fish communities under varying productivity of mesozooplankton and benthos, and top‐down forcing from fishing. We outline three strategies for coupling FEISTY with biogeochemical model output and discuss future directions and open issues.